Nanocarriers: A novel strategy for the delivery of CRISPR/Cas systems - Hejabi, Faranak; Abbaszadeh, Mohammad Sadegh; Taji, Shirinsadat; O’Neill, Andrew; Farjadian, Fatemeh; Doroudian, Mohammad (Frontiers in Chemistry, 2022)
In recent decades, clustered regularly interspaced short palindromic repeat/CRISPR-associated protein (CRISPR/Cas) has become one of the most promising genome-editing tools for therapeutic purposes in biomedical and medical applications. Although the CRISPR/Cas system has truly revolutionized the era of genome editing, the safe and effective delivery of CRISPR/Cas systems represents a substantial challenge that must be tackled to enable the next generation of genetic therapies. In addition, there are some challenges in the in vivo delivery to the targeted cells/tissues. Nanotechnology-based drug delivery systems can be employed to overcome this issue. This review discusses different types and forms of CRISPR/Cas systems and the current CRISPR/Cas delivery systems, including non-viral carriers such as liposomes, polymeric, and gold particles. The focus then turns to the viral nanocarriers which have been recently used as a nanocarrier for CRISPR/Cas delivery.